2005
DOI: 10.2105/ajph.2004.042994
|View full text |Cite
|
Sign up to set email alerts
|

The Seattle-King County Healthy Homes Project: A Randomized, Controlled Trial of a Community Health Worker Intervention to Decrease Exposure to Indoor Asthma Triggers

Abstract: Community health workers reduced asthma symptom days and urgent health services use while improving caregiver quality-of-life score. Improvement was greater with a higher-intensity intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
311
3
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 362 publications
(329 citation statements)
references
References 41 publications
(43 reference statements)
13
311
3
1
Order By: Relevance
“…Although some studies have indicated that education alone is an effective intervention, the preponderance asthma intervention studies indicate that education alone has not been effective in changing parental behaviors that affect asthma risk factors (Krieger et al, 2005;Wu and Takaro, 2007). While our results do not markedly change this conclusion, it is notable during the intervention phase of this study that the short-term (6 weeks to 4 months) effect of education was indistinguishable from the effect of cleaning on allergen levels in subsequent pre-cleaning samples.…”
Section: Allergen Interventioncontrasting
confidence: 87%
See 1 more Smart Citation
“…Although some studies have indicated that education alone is an effective intervention, the preponderance asthma intervention studies indicate that education alone has not been effective in changing parental behaviors that affect asthma risk factors (Krieger et al, 2005;Wu and Takaro, 2007). While our results do not markedly change this conclusion, it is notable during the intervention phase of this study that the short-term (6 weeks to 4 months) effect of education was indistinguishable from the effect of cleaning on allergen levels in subsequent pre-cleaning samples.…”
Section: Allergen Interventioncontrasting
confidence: 87%
“…Many studies, however, have not investigated the suite of allergens typically present in households, or the cost and effort involved in implementation, and many studies have expressed concerns about sustainability over time (Wu and Takaro, 2007). Given the multiple risk factors and increasing burden that asthma places on families and communities, it is important to test the efficacy of intervention strategies that affect the suite of common risk factors and can be implemented by a diverse population of residents, including those from low-income and/or non-English-speaking communities that bear the largest burden of this chronic disease (Takaro et al, 2004;Krieger et al, 2005;Levy et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Two of four RCTs demonstrated a significant decrease relative to control, 40,53 and two showed no significant decrease relative to control. 54,55 Of the four pre-post studies measuring this outcome, three demonstrated a statistically significant decrease, 41,44,45 and one showed a non-significant increase. 46 …”
Section: Emergency Department Visitsmentioning
confidence: 94%
“…There are significant benefits to integrating CHWs into the PCMH. Namely, clinical outcomes improve when CHWs are integrated into primary care teams [3][4][5][6][7]. Additionally, CHW-based interventions have demonstrated reduced health care use and costs for chronic care conditions [5,6,8,9].…”
Section: Purposementioning
confidence: 99%